2015
DOI: 10.1152/ajpendo.00480.2014
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378 regulates oocyte maturation via the suppression of aromatase in porcine cumulus cells

Abstract: Pan B, Toms D, Shen W, Li J. MicroRNA-378 regulates oocyte maturation via the suppression of aromatase in porcine cumulus cells. Am J Physiol Endocrinol Metab 308: E525-E534, 2015. First published January 27, 2015; doi:10.1152/ajpendo.00480.2014.-We sought to investigate whether miR-378 plays a role in cumulus cells and whether the manipulation of miRNA levels in cumulus cells influences oocyte maturation in vitro. Cumulus-oocyte complexes (COCs) from ovarian follicles had significantly lower levels of precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 65 publications
5
50
0
1
Order By: Relevance
“…A putative involvement of miR-378 in regulating luteal cell survival in bovine has been suggested but not proven [23]. However, in the pig, miR-378 targets aromatase and progesterone receptor in granulosa cells and regulates both ovarian estradiol production and oocyte maturation [24], [25], [26]. Finally, another of the miRNAs investigated in our study, mir-222, may reportedly regulate steroidogenesis of granulosa cells [27].…”
Section: Discussionmentioning
confidence: 64%
“…A putative involvement of miR-378 in regulating luteal cell survival in bovine has been suggested but not proven [23]. However, in the pig, miR-378 targets aromatase and progesterone receptor in granulosa cells and regulates both ovarian estradiol production and oocyte maturation [24], [25], [26]. Finally, another of the miRNAs investigated in our study, mir-222, may reportedly regulate steroidogenesis of granulosa cells [27].…”
Section: Discussionmentioning
confidence: 64%
“…It is noted that some miRNAs sponged by circRNAs have been shown to control cumulus cell function, oocyte maturation, and early embryo development. For example, miRNA-224 targeted by circRNA3798 in cumulus cells (Li et al, 2017b), miRNA-21 bound by circRNA193 (Wright et al, 2016), and miRNA-378 bound by circRNA2982 (Pan et al, 2015) in oocytes. Altogether, these results demonstrate that circRNAs identified in both porcine cumulus cells and oocytes could have similar effects of miRNA sponge as those observed in other cellular contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Different miRNA expression levels were reported during follicle development in different mammalian species with potential involvement in follicle growth, ovulation, steroidogenesis, and follicular‐luteal transition (Donadeu, Schauer, & Sontakke, ). Recently, functional analysis studies in porcine oocytes reported specific miRNAs, such as miR‐378 (Pan, Toms, Shen, & Li, ), miR‐21 (Wright, Hale, Yang, Njoka, & Ross, ), miR‐224 (X. Li, Wang, Sheng, & Wang, ), and miR‐574 (Pan, Toms, & Li, ) regulate oocyte maturation by targeting specific transcripts.…”
Section: Discussionmentioning
confidence: 99%